1982
DOI: 10.1083/jcb.94.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a factor that promotes neurite outgrowth: evidence linking activity to a heparan sulfate proteoglycan.

Abstract: Rat sympathetic neurons, plated onto extracellular matrix produced by cultured bovine corneal endothelial cells, rapidly extended neurites in the absence of nerve growth factor (NGF). The response was unaffected by antiserum to NGF. Rapid outgrowth also occurred when sympathetic neurons were plated onto polylysine-coated surfaces that had been exposed to serum-free medium conditioned by corneal endothelial cells (CMsF). A response was seen even when the neurons were cultured without serum. When plated onto a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(116 citation statements)
references
References 75 publications
(81 reference statements)
3
112
1
Order By: Relevance
“…Recently, several independent investigations have reported that heparan sulfate proteoglycans are concentrated in the basal lamina at the neuromuscular junction (2), are present in cholinergic synaptic vesicles (7, 10, 43), show an unusually high avidity for the synaptic form of acetylcholinesterase (47), and may function as substrate-attached nerve growth factors, even for neurons that do not respond to conventional nerve growth factor (27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several independent investigations have reported that heparan sulfate proteoglycans are concentrated in the basal lamina at the neuromuscular junction (2), are present in cholinergic synaptic vesicles (7, 10, 43), show an unusually high avidity for the synaptic form of acetylcholinesterase (47), and may function as substrate-attached nerve growth factors, even for neurons that do not respond to conventional nerve growth factor (27).…”
Section: Discussionmentioning
confidence: 99%
“…This band is converted, upon reduction, to two bands with Mrs of ~400,000 and ~ 200,000, appropriate for the heavy and light chains of LA. An earlier characterization of the motoneuron NOPA from MCM indicated that it was similar in its mode of action, size, density and enzymatic susceptibilities to a 'neurite outgrowth-promoting factor' from bovine corneal endothelial cell conditioned medium (BCE-CM) [3,9]. It has recently been reported that immunoprecipiration of LA from BCE-CM, as well as several other types of conditioned media, eliminates the ability of these conditioned media to promote neurite outgrowth by rat sympathetic neurons [10].…”
Section: Fracti Onmentioning
confidence: 99%
“…Neurite outgrowth depends upon ATP produced by glycolysis, which is actively suppressed by nitric oxide [180]. On the other hand, heparan sulfate plays an essential role in neurite outgrowth; several different sulfated glycosaminoglycans will stimulate growth-factor induced neurite outgrowth [181], and heparan sulfate supplied to the medium stimulates neurite outgrowth even in the absence of growth factors [182]. Once again, there is a compelling reason to produce sulfate, and clear justification not to produce nitric oxide.…”
Section: Enos and Sulfated Glycosaminoglycan Synthesismentioning
confidence: 99%